DISPENSASI NIKAH PASCA TERBIT UU NO. 16 TAHUN 2019 DI PENGADILAN AGAMA PROBOLINGGO - Nur Izah Fitriah; Abu Yazid Adnan Quthny; Imam Syafi’i (STAI Asy-Syukriyyah, 2023)
Child marriage is an interesting phenomenon to discuss. There have been many government efforts in dealing with the rampant cases of child marriage in Indonesia. One of them is by enacting the Marriage Law regarding the age limit for marriage. The change in the age limit for marriage regulated in laws and regulations to 19 years for both men and women has actually increased the number of child marriages in Indonesia. This research is a qualitative research with a case study type of research, namely in the Religious Court of Probolinggo City. From the research that has been done, the authors can conclude that even though the age limit for marriage has been regulated in the Marriage Law, a marriage dispensation policy for those w ho still wish to marry under the specified age can still be issued by a judge with various considerations. It cannot be denied that the existence of a marriage dispensation has actually become a boomerang for the effectiveness of the Marriage Law concerning the marriage age limit that has been made. Lawmakers need more attention to further reinforce existing regulations so that the marriage dispensation is not used as a way out for people who want to get married at an early age.